Linguistic Meaning Versus Pragmatic Meaning - Awwad, Mohammad (European Scientific Journal, ESJ, 2017)
A critical gap between linguistic specifications and context-relevant interpretation has existed ever since linguists sought to investigate meaning. As a matter of fact, English language has gained an unprecedented momentum over the last decades, and the ultimate aim of English language teaching has revolved around fostering the students’ ability to communicate proficiently in English. In this realm, much emphasis was given on the development of learners’ oral skills; however, those efforts were watered down on the progression of linguistic competence on the expense of communicative competence. In an attempt to bridge this gap, this study adopted Grice’s Cooperative Principle (1975) and embodied examples on how participants breach and neglect maxims upon which the Cooperative principle rests. For this aim, the study was carried on 100 English major students enrolled in the TEFL class at the Lebanese University (fifth branch); the investigation was carried over a period of four months in spring 2015- 2016. The results revealed that despite the subjects’ adequate linguistic proficiency in English, EFL learners still fall behind attaining pragmatic competence. The study endorses recommendations for EFL learners, teachers, and curriculum designers.